2023
DOI: 10.3390/biology12030454
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Effects of Whole-Body versus Local Dynamic Electrostimulation of the Abdominal Muscles in Healthy People Assessed by Ultrasound: A Randomized Controlled Trial

Abstract: Dynamic electrostimulation consists of the application of local or global electrostimulation together with physical exercise. This study aimed to investigate the immediate effects of a dynamic electrostimulation session on the thickness of the abdominal musculature, inter-rectus distance, heart rate, blood pressure, and body temperature, and to identify possible differences in its form of application. A total of 120 healthy participants were divided into three groups: the whole-body electrostimulation group, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 70 publications
(128 reference statements)
0
2
0
Order By: Relevance
“…This aspect might have contributed to the decision to deem at least untreated hypertension ( Kemmler et al, 2019 ) an absolute contraindication for commercial, non-medical WB-EMS. To our best knowledge, apart from a few studies that reported results of acute effects of WB-EMS on blood pressure (BP) as a secondary study outcome ( Hoshiai et al, 2021 ; Cassemiliano et al, 2022 ; Alvarez-Barrio et al, 2023 ), no further study has focused on blood pressure changes related to WB-EMS. The fact that the majority of clients of the large commercial German WB-EMS facilities are middle aged to older people ( EMS-Training.de, 2017 ), i.e., a cohort with a high prevalence of hypertension ( Neuhauser et al, 2016 ; Neuhauser et al, 2017 ), illustrates the relevance of providing evidence on acute WB-EMS induced effects on BP in middle aged-older people.…”
Section: Introductionmentioning
confidence: 99%
“…This aspect might have contributed to the decision to deem at least untreated hypertension ( Kemmler et al, 2019 ) an absolute contraindication for commercial, non-medical WB-EMS. To our best knowledge, apart from a few studies that reported results of acute effects of WB-EMS on blood pressure (BP) as a secondary study outcome ( Hoshiai et al, 2021 ; Cassemiliano et al, 2022 ; Alvarez-Barrio et al, 2023 ), no further study has focused on blood pressure changes related to WB-EMS. The fact that the majority of clients of the large commercial German WB-EMS facilities are middle aged to older people ( EMS-Training.de, 2017 ), i.e., a cohort with a high prevalence of hypertension ( Neuhauser et al, 2016 ; Neuhauser et al, 2017 ), illustrates the relevance of providing evidence on acute WB-EMS induced effects on BP in middle aged-older people.…”
Section: Introductionmentioning
confidence: 99%
“…NMES causes muscles to contract by activating muscle tissue and/or nervous cells (Lake 1992 ). The literature describes two main types of NMES: whole-body electromyostimulation (WB-EMS) and local NMES (Álvarez-Barrio et al 2023 ). WB-EMS is delivered using electrodes attached to the opposite sides of the body and stimulates the agonist and antagonist muscles at the same time (Filipovic et al 2012 ).…”
Section: Introductionmentioning
confidence: 99%